A tributação de lucros auferidos por controladas no exterior e a interpretação do artigo 7º dos Tratados para Evitar a Dupla Tributação - Lima, Larissa Pimentel de (2018)
This paper’s purpose is to analyze the application of the legal regime for the taxation of profits obtained abroad in cases involving companies located in countries that have signed a Treaty to Avoid Double Taxation (DTTs). Current Brazilian legislation establishes the prevalence of international treaties and conventions over domestic legislation. The Brazilian Federal Revenue Service understands that there is a supposed compatibility between the section 74 of Provisory Measure No. 2158 (taxation of foreign profits) and DTTs, so that the taxation of these profits earned abroad is due by Brazilian companies. Moreover, despite change in the legislation with Law No. 12,973/2014, the discussions of the past remain equally applicable, since this issue was not addressed in the text of the new Law. . In the present work, we intend to analyze the possibility of taxation of the profits obtained by the subsidiaries located in countries that have DTTs with Brazil in light of the new legal regime introduced by Law 12,973/2014, in order to guarantee greater legal certainty for the taxpayers. Our conclusion is that the application of DTTs should be sustained and taxation provided in Law 12,973/2014 should not be applicable in this situation, but this lack of harmony generates insecurity for the taxpayer and complexity in the interpretation of the rules. Thus, there is high expectation that litigation in our administrative and judicial courts will continue on this issue